A Simplex-Type Algorithm for Linear and Quadratic Programming--A Parametric Procedure - Jagannathan, R. (Econometrica, 1966)
A computational procedure based on the results of Barankin and Dorfman [1], for minimising a convex quadratic function subject to linear constraints is developed. The applicability of the proposed procedure for linear programming problems is indicated.